Development of Criticality in Thought: A Conceptual Framework for Online Student Discussion Forums in Higher Education - Nadya Shaznay Patel (Cranmore Publishing, 2021)
Assessing student understanding and extending student learning beyond the face-to-face or synchronous online lesson is commonly done with the use of online discussion forums. However, the challenge reported by tutors of higher education has always been the lack of active participation and critical engagement by students unless the task is graded formally. Researchers have been investigating various approaches to facilitate effective learning experiences such that students are motivated to engage others when they are tasked to partake in such asynchronous discussions. This paper explores how I sought to engage my Engineering undergraduate students, reading a critical thinking and writing module taught in a blended learning environment, in online discussion forums with the adoption of the Paul-Elder critical thinking framework. The aim was to develop higher levels of criticality in thought in students' forum responses, while demonstrating the application of the critical thinking tools, such that they were able to collaboratively construct knowledge and deepen their conceptual understanding of Engineering leadership. Results of the analysis found that students were engaged in spontaneous dialogic discussions in the form of repeated extended posts published in the online discussion forums. Furthermore, analysis of student critical reflection essays also confirmed that the online discussion forums, with a deliberate use of the tools of the framework, had contributed to their development of critical thinking skills to deepen their understanding. This paper concludes with a recommendation for tutors of higher education to make the assessment of students' critical reflection or critical thinking skills visible for students with a proposed conceptual framework for online discussion forums.